(untitled) (Applied Biological Research, 2018)
The present study was aimed to assess the bioefficacy of rhizobacteria isolated from walnut (Juglans regia) grown in North Western Himalayas against five fungal phytopathogens so that they may, in future, be exploited as biocontrol agents against fruit crop diseases. Ninety eight rhizobacterial isolates were isolated from walnut rhizosphere in major walnut growing areas of Kashmir. The siderophore & HCN production and chitinase activity were detected in 53, 82 and 35 isolates, respectively. In vitro assessment of rhizobacteria for biocontrol efficacy against 5 fungal pathogens viz., Dematophora necatrix, Alternaria solani, Pythium aphanidermatum, Fusarium oxysporum and Phytophthora capsici revealed that most of the rhizobacterial isolates exhibiting growth inhibition of various fungal pathogens belonged to the genus Bacillus. In present study, 23, 20, 19, 21 and 20 isolates were found antagonistic to D. necatrix, A. solani, F. oxysporum, P. aphanidermatum and P. capsici, respectively, with maximum inhibition in each respective case by isolate WI 90 (66%), WI 63 (55.6%), WI 62 (43.8%), WI 63 (45.5%) and WI 65 (49%). Twelve most effective isolates were morpho-biochemically and molecularly characterized and on the basis of 16S rDNA sequencing were identified as Bacillus licheniformis (isolates WI 90, Bacillus subtilis (isolates WI 63 and WI 65), Bacillus tequilensis (isolate WI 62), Bacillus cereus (isolate WI 36), Micrococcus luteus (isolates WI 12, WI 41 and WI 80), Micrococcus yunnanensis (is